Philippines : Fostering More Inclusive Growth - World Bank (World Bank, Washington, DC, 2017)
The main report is organized into three parts: part one provides the overall context by describing the level and evolution of poverty and inequality in the Philippines and by analyzing the factors that could be weakening the link between economic growth and poverty reduction. It also provides a brief profile of the poor. Part two addresses the first strategic component for fostering inclusive growth, which refers to the enhancement of income opportunities and ensuring greater labor mobility for the poor. It begins by reviewing recent economic developments, with particular attention to employment generation, and evaluates the potential of key economic sectors to generate growth and productive employment. Part two then turns to the related challenge of ensuring labor mobility, identifying signs of labor market segmentation and factors that may be responsible for labor market rigidities which inhibit the fluid movement of workers toward the most productive activities. Part three discusses the other main component of fostering inclusive growth, which is to ensure that workers and households are well-equipped to take advantage of productive employment opportunities. It reviews the current state of health, education, and social protection in the Philippines and proposes measures for strengthening social service delivery.